2011
DOI: 10.1097/mpa.0b013e31821fde24
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of High-Intensity Focused Ultrasound in Advanced Pancreatic Cancer

Abstract: High-intensity focused ultrasound is safe and effective, which induced excellent local tumor control in most patients with advanced PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 20 publications
5
54
0
7
Order By: Relevance
“…In remaining studies, HIFU was used as adjuvant treatment to RT or systemic CHT. In advanced pancreatic cancer, HIFU could provide significant relief of cancer pain (56)(57)(58)(62)(63)(64) and significant improvement of the Karnofski performance score (KPS) (21,64).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In remaining studies, HIFU was used as adjuvant treatment to RT or systemic CHT. In advanced pancreatic cancer, HIFU could provide significant relief of cancer pain (56)(57)(58)(62)(63)(64) and significant improvement of the Karnofski performance score (KPS) (21,64).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…4 From 2003 to 2014, series of studies have been published regarding Asian patients with advanced PC who were treated by US-guided HIFU (USgHIFU) with good clinical results. [4][5][6] Despite the great number of Asian studies, there are only a few cases with Caucasian patients. 7,8 All of these studies showed that USgHIFU ablation is a feasible, safe and effective treatment for pancreatic cancer with a crucial clinical benefit for the patients in terms of reduction of tumor volume and pain intensity.…”
Section: Opinionmentioning
confidence: 99%